Video analysis with youtube platform for Physical Education, Health, and Recreation students’s Higher Order Thinking Skills (HOTs) - Friskawati, Gita Febria; Supriadi, Dedi (Journal Sport Area, 2022)
Learning using technology-based media has become the main thing in learning in the 4.0 era to support high-level life skills, one of which is thinking skills. The purpose of this study is to re-prove the use of video analysis, especially using the Youtube platform for students' Higher Order Thingking Skills (HOTs). The study used an experimental design with a factorial design in a population of 312 PJKR level IV students who were taking Sports Pedagogy lectures. The sample consisted of 79 people in the experimental group and 80 people in the control group who were taken using cluster random sampling technique. The research was conducted from April 2020 to July 2020 when online lectures were conducted during the Covid 19 Pandemic with 12 meetings. The results show that there are differences in student HOTs in the group that uses video analysis with the Youtube platform and those that do not. The difference in HOTs is also seen in gender groups. HOTs in students can be improved through video analysis on the Youtube platform with learning stages that contain the HOTs concept, namely Concept, Analitycal, Understanding Knowlede, and Create.